Strategic development of a quality PE system in Cambodia - Nishiyama, Naoki (Universitas Negeri Yogyakarta, 2025)
Cambodia is currently undergoing comprehensive education reform, with Physical Education (PE) emerging as a distinct and strategically important area. This study explores the structural and systemic development of PE within Cambodia's Ministry of Education, Youth and Sport (MoEYS), emphasizing the role of international collaboration, particularly through the NGO Hearts of Gold (HG) and the Japan International Cooperation Agency (JICA). Since 2006, several initiatives have been implemented to develop PE curricula and teacher training systems across primary, lower secondary, and upper secondary levels. However, despite policy progress, PE implementation remains inconsistent due to gaps in teacher training, unclear curriculum alignment, and inter-departmental coordination. This study uses a qualitative, documentary-based approach to analyze curriculum frameworks, institutional structures, and training systems. Findings highlight the critical need for integrated planning among key departments (DPESS, NIPES, and GDS) and a consistent training pipeline for PE teachers. Moreover, the study identifies a lack of pedagogical content in earlier PE classes, where activities were limited to basic physical drills without educational objectives. The research proposes a strategic plan that focuses on improving curriculum implementation, reinforcing teacher training through pre-service and in-service alignment, and ensuring systemic oversight for sustainable development. Ultimately, this paper advocates for a holistic PE system that is inclusive, quality-oriented, and aligned with Cambodia’s broader educational reforms, to foster lifelong physical literacy and student development.